Analisis SWOT Strategi Pemasaran Produk Perbankan Syariah di Era Society 5.0 (Studi Kasus PT Bank Syariah Indonesia KC Bengkulu S Parman) - Aini, Hajjatul; Hak, Nurul; Sumarni, Yenti (Universitas Batanghari Jambi, 2024)
The purpose of this research is to determine the supporters, obstacles and efforts of PT Bank Syariah Indonesia KC Bengkulu S Parman in marketing BSI Easy Wadiah Savings products in overcoming the marketing of BSI Easy Wadiah Savings products in the era of society 5.0. This research uses qualitative methods by collecting primary data, direct interviews with BSI and secondary data in the form of journals, scientific works and books related to the discussion. The data analysis technique used is descriptive analysis method and SWOT analysis. The research results showed that the identification of these internal factors resulted in 5 (five) strengths and 1 (one) weakness. Meanwhile, the results of identifying these external factors produced 4 (four) opportunities and 2 (two) threats for PT Bank Syariah Indonesia KC Bengkulu S Parman.